A new approach for Solving a nonlinear system of second-order BVPs - Amoozad, Taher; Abbasbandy, Saeid; Allahviranloo, Tofigh; Rostamy Malkhalifeh, Mohsen (Mathematical Modelling and Analysis, 2024)
In this paper, we introduce a new approach based on the Reproducing Kernel Method (RKM) for solving a nonlinear system of second-order Boundary Value Problems (BVPs) without the Gram-Schmidt orthogonalization process. What motivates us to use the RKM without the Gram-Schmidt orthogonalization process is its easy implementation, elimination of the Gram-Schmidt process, fewer calculations, and high accuracy. Finally, the compatibility of numerical results and theorems demonstrates that the Present method is effective.